Tumor Therapy: Bifunctional Platinated Nanoparticles for Photoinduced Tumor Ablation (Adv. Mater. 46/2016). Issue 46 (December 2016) - Guo, Zhengqing; Zou, Yelin; He, Hui; Rao, Jiaming; Ji, Shuangshuang; Cui, Xiaoneng; Ke, Hengte; Deng, Yibin; Yang, Hong; Chen, Chunying; Zhao, Yuliang; Chen, Huabing
Abstract : Self‐assembled nanoparticles of platinated Bodipy, described by H. B. Chen on page 10155, produce both singlet‐to‐triplet and nonradiative transitions through the heavy‐atom effect and a d–d energy‐band transition of the platinum under light irradiation, accompanied by an ultralow radiative transition. These transitions allow the platinated nanoparticles to generate both singlet oxygen and the photothermal effect for synergistic photodynamic and photothermal treatments with tumor ablation.